2000
DOI: 10.1016/s0029-7844(00)00918-2
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1 and HLA-DPB1 genotypes in severe preeclampsia

Abstract: These data suggest that women who have the HLA-DQB1*04 allele might be susceptible to preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…But they concluded that HLA-DQB1*0503 may be a marker in high blood pressures in pregnancy ( 21 ). In another study, Honda et al investigated the relationship of HLA-DQB1 and HLA-DPB1 to severe pregnancies and their data suggested that women who have the allele HLA-DQB1*04 might be susceptible to preeclampsia ( 22 ). Moreover, Ooki et al carried out an experiment in order to probe HLA class II alleles among couples with severe preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…But they concluded that HLA-DQB1*0503 may be a marker in high blood pressures in pregnancy ( 21 ). In another study, Honda et al investigated the relationship of HLA-DQB1 and HLA-DPB1 to severe pregnancies and their data suggested that women who have the allele HLA-DQB1*04 might be susceptible to preeclampsia ( 22 ). Moreover, Ooki et al carried out an experiment in order to probe HLA class II alleles among couples with severe preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Few publications have addressed the relationship between HLA genotypes and gestation period. However, a recent study reports that DQB10201 non‐asp 57 correlates with abortion [11] and that the DQB104 allele is associated with pre‐eclampsia [12]. The relationship between gestation period and risk of developing T1D in childhood is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a genetic basis for pre‐eclampsia has also been suggested (25, 27). Several studies have examined the possible association between HLA system and pathogenesis of pre‐eclampsia (3–5). Recently, the only polymorphic HLA class I antigen expressed on the interface of the fetal–maternal HLA‐C is taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal exclusion mapping suggested a role for genes on chromosome 1, 3, 9, or 18 (1), and a genomewide scan of 15 affected pedigrees identified a candidate region on chromosome 4 (2). Candidate genes such as human leukocyte antigen (HLA)‐DR, HLA‐DRB1, HLA‐DQB1, HLA‐DPB1 and currently, the only known polymorphic HLA expressed on fetal trophoblast, HLA‐C, has also been studied (3–6). These studies indicated that various genes may predispose to the pathogenesis of pre‐eclampsia.…”
Section: Introductionmentioning
confidence: 99%